Distribution of Blood Pressure and Evaluation of Risk Factors for Hypertension among Women in Turkey - U Ayranci; A Unsal; M Tozun (Tehran University of Medical Sciences, 2008)
Background: The aim was to investigate the distribution of blood pressure (BP) and evaluate some of the risk factors connected to hypertension. This study was deemed important and relevant due to the increasing importance of hypertension and cardiovascular diseases.Methods: This cross-sectional survey was conducted on 4,446 women aged 40 and over who had presented themselves with any number and form of health reasons to any of the 19 primary health care (PHC) centers in a district of western Turkey between February 1st and March 31st, 2006. The Seventh Report of the Joint National Committee (JNC 7) was used for BP measurements and classifications. We performed Chi Square (x2) test, variance (ANOVA) and Logistic Regression Analysis with the statistical importance of P≤ 0.05.Results: The respondents' BPs showed an increase with age (P< 0.001, for each one). 56.7% of the study group had high BP. An advanced age (P< 0.001), obesity (P< 0.001), family history (P< 0.01), smoking (P< 0.01), hypercholesterolemia (P< 0.01), and not having health insurance (P< 0.01) were all deemed important risk factors for hypertension (P< 0.001). 6.6% of women had not had their BP previously measured. 24.5% of whose BP was high were not aware of their high BPs.Conclusion: The number of the respondents at risk to hypertension was high and many people reported that they were unaware of hypertension and its risk factors. This shortfall in information and knowledge needs to be addressed by health education programs such as BP screening studies and periodical examinations targeting those at higher risk.